2015
DOI: 10.1016/j.stem.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Thyroid Function by Transplantation of Differentiated Pluripotent Stem Cells

Abstract: Differentiation of functional thyroid epithelia from pluripotent stem cells (PSCs) holds the potential for application in regenerative medicine. However, progress toward this goal is hampered by incomplete understanding of the signaling pathways needed for directed differentiation without forced over-expression of exogenous transgenes. Here we use mouse PSCs to identify key conserved roles for BMP and FGF signaling in regulating thyroid lineage specification from foregut endoderm in mouse and Xenopus. Thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(246 citation statements)
references
References 40 publications
(54 reference statements)
9
233
0
1
Order By: Relevance
“…Postiglione et al, 2002). More recently (Longmire et al, 2012), it was shown that Fgf2 and Bmp4 are necessary and sufficient for the directed differentiation of mouse and human ESCs and human induced pluripotent stem cells (iPSCs) into functional thyrocytes, provided that cells are pre-programmed to definitive endoderm (Kurmann et al, 2015) (Fig. 3B).…”
Section: Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Postiglione et al, 2002). More recently (Longmire et al, 2012), it was shown that Fgf2 and Bmp4 are necessary and sufficient for the directed differentiation of mouse and human ESCs and human induced pluripotent stem cells (iPSCs) into functional thyrocytes, provided that cells are pre-programmed to definitive endoderm (Kurmann et al, 2015) (Fig. 3B).…”
Section: Reviewmentioning
confidence: 98%
“…However, although several protocols are now at hand to generate thyroid progenitors and functional follicles from human ESCs or iPSCs (Kurmann et al, 2015;Ma et al, 2015), the field needs further advances (as reviewed by Hollenberg et al, 2016) to make this a realistic possibility. For example, the pool of Nkx2-1 + /Pax8 + thyroid progenitors generated by these approaches is small compared with the number of coinduced lung progenitors, and sorting and enriching precursor cells currently requires genetic labeling (Kurmann et al, 2015). Evidently, additional factors that are of importance for the specification process are still to be identified.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also demonstrated that this mechanism may work in the thyroid differentiation. Greater expression of HIF-1a and HIF-2a at all time points together with FGF2 which was a direct transcriptional target of HIFs (Simon et al, 2008) and played an important role in specifying the thyroid lineage (Kurmann et al, 2015) revealed their possible involvement in this promotion by hypoxia. However, because the detail molecular mechanism of thyroid differentiation from murine iPS cells still remains unknown, the topics about whether other mechanisms or factors may get involved in this promotion need our further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…5A-D). As one of the important downstream genes of HIFs (Simon et al, 2008), fibroblast growth factor 2 (FGF2) is considered to be necessary for thyroid lineage specification from mouse pluripotent stem cells (Kurmann et al, 2015). In order to avoid the interference of exogenous factors, we measured mRNA expression of FGF2 under both conditions with HIFs and the result indicated that hypoxia also significantly increased the level of FGF2 at all the time points (Fig.…”
Section: Hypoxia Promotes Thyroid Endoderm Inductionmentioning
confidence: 99%